Disseminated Tuberculosis and Chronic Mucocutaneous Candidiasis in a Patient with a Gain-of-Function Mutation in Signal Transduction and Activator of Transcription 1 - Pedraza-Sánchez, Sigifredo; Lezana-Fernández, Jose Luis; Gonzalez, Yolanda; Martínez-Robles, Luis; Ventura-Ayala, María Laura; Sadowinski-Pine, Stanislaw; Nava-Frías, Margarita; Moreno-Espinosa, Sarbelio; Casanova, Jean-Laurent; Puel, Anne; Boisson-Dupuis, Stephanie; Torres, Martha (Frontiers in Immunology, 2017)
In humans, recessive loss of function mutations in STAT1 are associated with mycobacterial and viral infections, whereas gain of function (GOF) mutations in STAT1 are associated with a type of primary immunodeficiency related mainly, but not exclusively, to chronic mucocutaneous candidiasis (CMC). We studied and established a molecular diagnosis in a pediatric patient with mycobacterial infections, associated with CMC. The patient, daughter of a non-consanguineous mestizo Mexican family had axillary adenitis secondary to BCG vaccination and was cured with resection of the abscess at one-year old. At four years of age, she had a supraclavicular abscess with acid-fast staining bacilli identified in the soft tissue and bone, with clinical signs of disseminated infection and a positive Gene-X-pert test, which responded to anti-mycobacterial drugs. Laboratory tests of the IL-12/IFN-γ circuit showed a higher production of IL-12p70 in the whole blood from the patient compared to healthy controls, when stimulated with BCG and BCG + IFN-γ. The whole blood of the patient produced 35% less IFN-γ compared to controls assessed by ELISA and flow cytometry, but IL-17 producing T cells from patient were almost absent in PBMC stimulated with PMA plus ionomycin. STAT-1 was hyperphosphorylated at tyrosine 701 in response to IFN-γ and α, as demonstrated by flow cytometry and western blotting in fresh blood mononuclear cells and in Epstein-Barr virus lymphoblastoid cell lines (EBV-LCL); phosphorylation of STAT-1 in EBV-LCL from the patient was resistant to inhibition by staurosporine, but sensitive to ruxolitinib, a Jak phosphorilation inhibitor. Genomic DNA sequencing showed a de novo mutation in STAT1 in cells from the patient, absent in her parents and brother; a known T385M missense mutation in the DNA-binding domain of the transcription factor was identified and it is a GOF mutation. Therefore, GOF mutations in STAT1 can induce susceptibility not only to fungal but also to mycobacterial infections, by mechanisms to be determined.